2012
DOI: 10.1172/jci64397
|View full text |Cite
|
Sign up to set email alerts
|

Spleens of myelofibrosis patients contain malignant hematopoietic stem cells

Abstract: Cancer stem cell behavior is thought to be largely determined by intrinsic properties and by regulatory signals provided by the microenvironment. Myelofibrosis (MF) is characterized by hematopoiesis occurring not only in the marrow but also in extramedullary sites such as the spleen. In order to study the effects of these different microenvironments on primitive malignant hematopoietic cells, we phenotypically and functionally characterized splenic and peripheral blood (PB) MF CD34 + cells from patients with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 43 publications
2
67
1
Order By: Relevance
“…30 This concept was recently validated by the observation that the spleen of PMF patients is uniquely enriched for PMF stem cells. 50 The great numbers of PMF stem cells observed in the spleen of the patients and the different TGF-b1 alteration signatures of BM and spleen described here suggest a model for the development of MF, according to which TGF-b1 released by the MK progeny of MF stem cells induce different TGF-b1 expression signatures in BM and spleen, which suppress normal hematopoiesis in BM and activate MF hematopoiesis in spleen (supplemental Figure 4). This model predicts that, in spite of the encouraging results obtained with JAK2 inhibitors in PMF, the disease will be better controlled by therapies combining JAK2 inhibitors with drugs, still to be identified, and that may reactivate normal hematopoiesis in BM.…”
Section: Discussionmentioning
confidence: 67%
“…30 This concept was recently validated by the observation that the spleen of PMF patients is uniquely enriched for PMF stem cells. 50 The great numbers of PMF stem cells observed in the spleen of the patients and the different TGF-b1 alteration signatures of BM and spleen described here suggest a model for the development of MF, according to which TGF-b1 released by the MK progeny of MF stem cells induce different TGF-b1 expression signatures in BM and spleen, which suppress normal hematopoiesis in BM and activate MF hematopoiesis in spleen (supplemental Figure 4). This model predicts that, in spite of the encouraging results obtained with JAK2 inhibitors in PMF, the disease will be better controlled by therapies combining JAK2 inhibitors with drugs, still to be identified, and that may reactivate normal hematopoiesis in BM.…”
Section: Discussionmentioning
confidence: 67%
“…Notably, propagation of human myeloid leukemia in vivo remains challenging, even for a subset of AML, a fully penetrant and deadly disease in patients. Besides the notoriously poor engraftment of MDS 37,140-142 and MPNs, 143,144 ;50% of AMLs fail to engraft immune-compromised hosts. 145 This fraction of "engrafter" cases could be further increased in AML by using new mouse lines that express a number of human cytokines that are poorly or not at all cross-reactive between mice and humans.…”
Section: Emerging Strategies To Improving the Modeling Of Human Myelomentioning
confidence: 99%
“…44 In addition, our laboratory has also reported the presence of greater numbers of malignant stem cells in the spleen compared with the peripheral blood of patients with MF. 16 Splenic endothelial cells express many hematopoietic factors, which may be insufficient to maintain the normal hematopoietic progenitor potential. MF hematopoietic progenitors, in contrast, are more sensitive to hematopoietic growth factors and microenvironmental cues because of the characteristic driver mutations and the subsequent activation of the JAK/STAT pathway.…”
Section: Org Frommentioning
confidence: 99%
“…The vascular lining cells within MF spleens are thought to serve as a supportive microenvironment for MF hematopoietic cells. [13][14][15][16] Barosi and coworkers have reported that the capillary, but not sinusoidal, vascular density was increased within the MF spleen, (CD206), and STAB2 (Stabilin-2) (H); RHOU (J). The expression of all genes was normalized to GAPDH, and the relative expression of a LC gene was calculated against that of SVEC, which was set as 1.…”
Section: Introductionmentioning
confidence: 99%